Implementasi Kurikulum Merdeka: Meningkatkan Sistem Pendidikan Indonesia? - Prada Destina Rahmadani; Diny Honggo Jati; Elia Ayu Pratama (Journal of Information Systems and Management (JISMA), 2024)
The aim of this study is to determine the importance of implementing the independent curriculum. This study report uses a descriptive qualitative method by listening and taking notes because the source of the information was obtained from one of the YouTube channels of the Directorate of Primary Schools entitled "Getting to Know the Implementation of the Independent Curriculum Closer". The results of this study explain that the development of the learning curriculum continues to change, from the school learning system with curriculum 13 to now the independent curriculum. The Merdeka Curriculum is able to improve the learning system so that it can recover from the crisis in the learning system. This research began with the emergence of a curriculum revolution that could change everyone's view of the learning system in educational units.